Back Cover: From Palladium to Brønsted Acid Catalysis: Highly Enantioselective Regiodivergent Addition of Alkoxyallenes to Pyrazolones (Angew. Chem. Int. Ed. 4/2017). Issue 4 (9th January 2017) - Zhou, Hui; Wei, Zhao; Zhang, Jinlong; Yang, Huameng; Xia, Chungu; Jiang, Gaoxi
Abstract : Two catalytic processes namely, palladium catalysis and Brønsted acid catalysis, lead to different alkylation products in the addition of alkoxyallenes to pyrazolones. In their Communication onpage 1077, G. Jiang et al. demonstrate how Pd catalysis provides branched allylic pyrazol‐5‐ones under mild conditions, whereas a chiral Brønsted acid catalyst gives the linear addition products.